Kullu: a scared journey from Nirmand to Rohtang - Chaudhry, Minakshi (ed.) (Kullu, District Cultural Council & District Dussehra Committee, 2015)
Kullu: a scared journey from Nirmand to Rohtang.
Keywords: Kullu; Himachal Pradesh